The impact of staff training on special educational needs professionals' attitudes toward and understanding of applied behavior analysis. (December 2019) - Smyth, Sinéad; Reading, Benjamin E; McDowell, Claire
Background: Research-based evidence points to the efficacy and value of applied behavior analysis (ABA) in meeting the needs of individuals with learning disabilities and autism. Nonetheless, public, government, and professional perception of ABA can be negative. The current study was designed to measure the impact of a short intervention on professionals' attitudes toward, and knowledge of, ABA. Method: Teachers and classroom assistants from two separate schools for children with severe learning difficulties completed a self-report survey on knowledge of and attitudes toward ABA. They were then presented with a 90-min training module designed to increase their knowledge of the history of ABA and their functional assessment skills. Following training, the self-report was readministered. Results: The mean scores for each group increased only after the training had been delivered. Discussion and conclusions: Further research is needed to address the impact of training on classroom practice.